The impact of time-of-day of measurement and morningness-eveningness as personality trait on sensory and perceptual-motor performance - Ivanec, Dragutin; Tomas, Jasmina (2012)
Performance in a variety of tasks can change depending on the time of the day. The aim was to investigate the assumption of possible interaction effect between time of day of measurement and morningness-eveningness as a stable personality trait. Assumption was that interaction effect will occur between morningness-eveningness and time of measurement. Morning types are assumed to show better sensory-motor performance in measurement taken during morning time, and worse during measurement during the evening time. Opposite trend was expected for evening types. Participants took part in the experiment twice: once in the morning (8-10 a.m.), and once in afternoon (18-20 p.m.). Within each session the first measure was pain threshold for mechanical pressure. Second measure was speed and accuracy in visual searching task. Independently of those two sessions information on participants’ morningness- eveningness traits was collected by questionnaire. Participants were divided in two independent groups: morning and evening type. The results did not confirm our assumptions. There were no interaction effects between type of personality and time of measurement. Both types showed similar pain sensitivity and the same performance on visual searching task, regardless of the time of measurement. In spite of lack of assumption confirmation, these results have methodological value. Probably there is no need to control for assumed interaction effect in planning research in the field of pain perception or sensory-motor performance.
Projekt MZOS
ENG